Les Sous-Regions Rurales de la Province Orientale dans la dynamique de l’histoire recente du Zaire: de 1960 à 1985 (cas du Bas-Uélé) - Denda-Sakala, Dieudonné Mily (Afrika Focus, 1996)
This study takes the Sub-Region of the Bas-Ulélé as an example of the recent history of the rural areas in Zaire. It gives a description from an insider’s point of view based on local research, results in a testimony relating the complete deterioration of rural potentialities in Zaire. The article describes how in the first years after independence, the rich natural resources and the colonial infrastructure brought prosperous development. From 1964 to 1966, however, the Simba-rebellion ravaged the area, destroying a great deal of the infrastructure and caused large-scale massacres among the local population. After the crushing of the rebellion, the subsequent revival was quickly halted by constant bureaucratic hindrances and interference from Mobutu’s MPR. "Zairisation " led to further deterioration of the economic infrastructure. From 1980 on, the Sub-Region was neglected more and more by the central government and even by its elected representatives. Finally, the liberalising of gold- prospecting withdrew farmers, schoolchildren and teachers form their normal activities leading only to more misery in the area. KEY WORDS: Development, Local Administration, Politics, Zaire